Incidence of Refeeding Syndrome in Critically Ill Children With Nutritional Support - Stéphanie Blanc; Tajnja Vasileva; Lyvonne N. Tume; Florent Baudin; Carole Chessel Ford; Corinne Chaparro Jotterand; Frederic V. Valla; Frederic V. Valla (Frontiers Media S.A., 2022)
IntroductionEarly enteral nutrition is recommended for critically ill children, potentially exposing those who are undernourished to the risk of refeeding syndrome. However, data on its incidence is lacking, and the heterogeneity of diagnostic criteria and frequent electrolyte disorders in this population make its diagnosis complex. In 2020, the American Society for Parenteral and Enteral Nutrition (ASPEN) developed consensus recommendations for identifying patients at risk and with refeeding syndrome. These state that undernourished children are considered at risk of refeeding syndrome; those who develop one significant electrolyte disorder (decrease ≥ 10% in phosphorus, potassium, and/or magnesium) within the first five days of nutritional support, combined with a significant increase in energy intake, are considered to have refeeding syndrome. The aim of this study was to determine the incidence of refeeding syndrome according to the ASPEN definition in critically ill children on nutritional support.Materials and MethodsA secondary analysis of two prospective cohorts conducted in a tertiary pediatric intensive care unit in France was undertaken, and additional data were retrospectively collected. Children included were those (0-18 years) admitted to the pediatric intensive care unit with a minimum of one phosphorus, potassium, and/or magnesium assay and who received exclusive or supplemental nutritional support. Undernourished children (body mass index z-score < -2 standard deviations) were considered at risk of refeeding syndrome. The ASPEN critiera were used to identify those with probable refeeding syndrome.ResultsA total of 1,261 children were included in the study, with 199 children (15.8%) classified as undernourished, who were at risk of refeeding syndrome. Of these, 93 children were identified as having probable refeeding syndrome, giving an overall incidence of 7.4%. The incidence rate among at-risk children was 46.7%. Most patients (58.1%) were classified as having severe refeeding syndrome.ConclusionRefeeding syndrome remains difficult to diagnose in critically ill children, due to frequent confounding factors impacting electrolyte plasma levels. These findings suggest that refeeding syndrome incidence may be high in undernourished children, and that refeeding syndromes can be severe. Further prospective studies using the ASPEN definition and risk criteria are required.